Bilingualism for the Emergence of Language Situation and Language Condition - Bibikhanum, Babashova; Gulayim, Nurumbetova (European Journal of Life Safety and Stability (2660-9630), 2023)
According to Hymes (1972), language socialization is the process through which a child or other beginner (of any age) develops communicative competence, enabling him or her to engage in meaningful interactions with others and otherwise take part in the social life of a particular society. The majority of the time, interactions with peers and relationships with older people are how language socialization takes place.[1:31].